Renal Arteriovenous Malformation - Gandhi, Shruti P.; Patel , Kajal; Pandya , Vaidehi; Raval, Manish (New Horizons in Medicine and Medical Research Vol. 11, 2022)
Renal arteriovenous malformations (AVMs) or arteriovenous fistulas (AVFs) represent an important group of entities for diagnostic consideration due to high morbidity associated with the disease. It is uncommon cause of hematuria. For safe and effective treatment it is important to evaluate radiographic findings and type of AVM in detail. The purpose of this book chapter to highlight main types of AVM, clinical presentation, imaging modalities and treatment options.